Experimental Research of Heat Carrier Parameters when Exposed to Electromagnetic Field of Super-High Frequency - I. G. Ershova; A. N. Vasiliev; D. V. Poruchikov (Сельскохозяйственные машины и технологии)
In order to evaluate the initial requirements for a coolant when designing an installation for obtaining the energy of the “water – ice” phase transition, it is necessary to conduct experimental studies on the thermophysical and electrophysical parameters of the coolant. The type of chosen coolant determines the power of the developed installation. (Research purpose) Experimental determination of the thermophysical and electrophysical parameters of the coolant when exposed to an electromagnetic field of super-high frequency, with the prospect of using this coolant in the developed installation. (Materials and methods) The authors used water and a saline solution of sodium chloride at a concentration of 1–20 percent as a coolant in the developed experimental installation for obtaining the energy of the “water-ice” phase transition. When exposed to an electromagnetic field of super-high frequency (microwave oven Mystery MMW-2315G) with a power of 800 watts and a magnetron frequency of 2450 megahertz, the treatment time was alternatively set at 30, 60 and 120 seconds. Measurements were taken of freezing temperature, pH of water and solutions, electrical conductivity, and salt concentration. (Results and discussion) It has been found that when a super-high-frequency electromagnetic field affects a sodium chloride solution at a concentration of 20 percent, its freezing temperature decreases from 16.6 degrees Celsius below zero to 18.5 degrees Celsius below zero, for a eutectic solution - from 21.2 degrees Celsius below zero to 25 degrees Celsius below zero, while pH and salt concentration increase, and specific electrical conductivity decreases as well. (Conclusions) The authors have selected an optimal coolant for the developed experimental installation: a saline solution of sodium chloride at a concentration of 20 percent and a freezing temperature of 16.6 degrees Celsius below zero. It is recommended to provide additional capacity for the electrophysical treatment of the coolant. It has been determined that after the super-high frequency electromagnetic treatment, the freezing temperature of the saline solution dropped to 18.5 degrees Celsius below zero.